Cu(I)/Ag(I)-mediated decarboxylative trifluoromethylation of arylpropiolic acids with Me3SiCF3 at room temperature. Issue 27 (7th July 2016) - Yang, Lingling; Jiang, Linlin; Li, Yaming; Fu, Xinmei; Zhang, Rong; Jin, Kun; Duan, Chunying
Abstract: A novel Cu(I)/Ag(I)-mediated decarboxylative trifluoromethylation of arylpropiolic acids with Me3 SiCF3 has been developed for the construction of Csp-CF3 bond under mild conditions. This method proceeds smoothly at room temperature and shows a widely functional compatibility, providing a series of corresponding trifluoromethylated acetylenyl-containing aromatics in good yields. Graphical abstract: